The Issue of Islamic Higher Education Development in Indonesia from 1945 to Present - Sugianto, Sugianto; Ansori, M Afif; Andari, An An; Pribadi, Joko; Nisa, Khairun (Yupa: Historical Studies Journal, 2024)
This research aims to analyze the issues surrounding the development of Islamic Higher Education through the application of literature review methodology. Literature review methodology involves collecting and analyzing relevant literature and references to understand the associated issues within the context of Islamic higher education institutions. The study adopts a qualitative approach by analyzing various literatures, journals, books, and related theoretical sources. The data obtained are descriptively analyzed to identify patterns and trends in the dynamics of Islamic higher education institutions. The findings reveal that these institutions face complex dynamics in addressing contemporary challenges. Furthermore, this abstract identifies challenges encountered by Islamic Higher Education institutions, such as competition with non-Islamic educational institutions, enhancing the quality of human resources, funding, and accreditation issues. These challenges require innovation and appropriate strategies to ensure the sustainability and success of Islamic Higher Education institutions. In conclusion, this abstract highlight the dynamics occurring within Islamic Higher Education institutions.